The Role of Vertebral Porosity and Implant Loading Mode on Bone-Tissue Stress in the Human Vertebral Body Following Lumbar Total Disc Arthroplasty. Issue 19 (1st October 2021) - Bonnheim, Noah B.; Adams, Mark F.; Wu, Tongge; Keaveny, Tony M.
Abstract : Study Design: Micro-computed tomography- (micro-CT-) based finite element analysis of cadaveric human lumbar vertebrae virtually implanted with total disc arthroplasty (TDA) implants. Objective: (1) Assess the relationship between vertebral porosity and maximum levels of bone-tissue stress following TDA; (2) determine whether the implant's loading mode (axial compression vs. sagittal bending) alters the relationship between vertebral porosity and bone-tissue stress. Summary of Background Data: Implant subsidence may be related to the bone biomechanics in the underlying vertebral body, which are poorly understood. For example, it remains unclear how the stresses that develop in the supporting bone tissue depend on the implant's loading mode or on typical inter-individual variations in vertebral morphology. Methods: Data from micro-CT scans from 12 human lumbar vertebrae (8 males, 4 females; 51–89 years of age; bone volume fraction [BV/TV] = 0.060–0.145) were used to construct high-resolution finite element models (37 μm element edge length) comprising disc-vertebra-implant motion segments. Implants were loaded to 800 N of force in axial compression, flexion-, and extension-induced impingement. For comparison, the same net loads were applied via an intact disc without an implant. Linear regression was used to assess the relationship between BV/TV, loading mode, and the specimen-specific change in stress caused by implantation. Results: The increase in maximum bone-tissue stress caused by implantation depended on loading mode ( P < 0.001), increasing more in bending-induced impingement than axial compression (for the same applied force). The change in maximum stress was significantly associated with BV/TV ( P = 0.002): higher porosity vertebrae experienced a disproportionate increase in stress compared with lower porosity vertebrae. There was a significant interaction between loading mode and BV/TV ( P = 0.002), indicating that loading mode altered the relationship between BV/TV and the change in maximum bone-tissue stress. Conclusion: Typically-sized TDA implants disproportionately increase the bone-tissue stress in more porous vertebrae; this affect is accentuated when the implant impinges in sagittal bending. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the textHigh-resolution finite element models of disc-vertebra-implant motion segments were constructed using micro-computed tomography data from human cadaveric lumbar vertebrae. Implants were loaded in axial compression, flexion-, and extension-induced impingement. The resulting insight into the bone biomechanics could inform implant designs, in vitro tests protocols, and patient selection for lumbar total disc arthroplasty.